2018
DOI: 10.1002/2017jd027819
|View full text |Cite
|
Sign up to set email alerts
|

Weak Cooling of Cold Extremes Versus Continued Warming of Hot Extremes in China During the Recent Global Surface Warming Hiatus

Abstract: Using daily maximum temperature (Tmax), minimum temperature (Tmin), and mean temperature data of 437 weather stations in China, we compared variations of the mean with extreme ends of probability distribution of temperatures in China from 1960 to 2015. Our analysis confirmed that annual mean Tmax and Tmin experienced warming hiatus in China after 1998. The warming hiatus is also reflected by the weak cooling of cold extremes across China, but hot extremes continue the significant warming trend nationally and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 60 publications
3
48
0
Order By: Relevance
“…China is susceptible to climate change (Chen and Zhai 2017). It was reported that the frequencies of warm days and warm nights have increased at rates of 0%-3.0% and 0%-4.0% per decade, respectively, in almost the entire region of China for the period 1961-2015 (Shi et al 2018), while the intensities of warm extremes have shown an asymmetric change pattern in China (Zhou et al 2016, Shen et al 2018. Spatially, warm extremes became significantly warmer in South China, northwestern North China, northeastern Northeast China, eastern Northwest China and eastern Southwest China.…”
Section: Introductionmentioning
confidence: 99%
“…China is susceptible to climate change (Chen and Zhai 2017). It was reported that the frequencies of warm days and warm nights have increased at rates of 0%-3.0% and 0%-4.0% per decade, respectively, in almost the entire region of China for the period 1961-2015 (Shi et al 2018), while the intensities of warm extremes have shown an asymmetric change pattern in China (Zhou et al 2016, Shen et al 2018. Spatially, warm extremes became significantly warmer in South China, northwestern North China, northeastern Northeast China, eastern Northwest China and eastern Southwest China.…”
Section: Introductionmentioning
confidence: 99%
“…Though, there are still debates on the global warming hiatus, it is virtually certain that the warming hiatus were more noticeable in regional scales at the Northern Hemisphere (NH): for example, mainland China and Eurasian continents (Duan and Xiao 2015, Guan et al 2015, Li et al 2015, Garfinkel et al 2017, Sun et al 2017, Xie et al 2017, Shen et al 2018. Compared to the studies on the terrestrial warming hiatus, less focus has been given to warming hiatus at marginal seas.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, most areas west of 108°E or south of 30°N were characterized by continual warming, rather than by a decelerated warming trend (Figures and ). It is likely that an increase in dryness or a decline in warm season precipitation in the southern China (Li et al ., ; Shen et al ., ) as well as the radiatively forced temperature effect in the western China (especially on the Tibetan Plateau) facilitated this continual warming (Ma et al ., ). Additionally, more than half of stations were characterized by monotonic temperature increase, which might also be directly related to continuous warming at the country level (Risbey et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier work, Wang et al (2010) analysed meteorological records in China for the period of 1961-2004 and showed that the warming trend started around 1980 in most stations and that this phenomenon gradually occurred later from north to south. Nevertheless, through applying the period of global warming "hiatus" for a priori justification to regional scales (Chen and Zhai, 2017), several recent studies pointed out that China also experienced a warming "hiatus" since 1998 (Li et al, 2015;Xie et al, 2017;Shen et al, 2018). In different regions, a strong warming "hiatus" in eastern China was observed during 1998-2013 (Chen and Zhai, 2017), especially in Northeast China (Sun et al, 2017), whereas an accelerated warming trend was detected on the Tibetan Plateau over the same period (Duan and Xiao, 2015;Ma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%